PHP5 and MySQL bible - Converse, Tim, 1961- (Bible., 2004)
This comprehensive tutorial and reference covers all the basics of PHP 5, a popular open source Web scripting language, and MySQL 4.012, the most popular open source database engineExplores why users need PHP and MySQL, how to get started, how to add PHP to HTML, and how to connect HTML Web pages to MySQLOffers an extensive tutorial for developing applications with PHP and MySQLIncludes coverage of how to install, administer, and design MySQL databases independently of PHP; exception and error handling; debugging techniques; PostgreSQL database system; and PEAR database functionsThe authors pr.